use the properties of operations to solve for multiplying and dividing to solve (-2)x (1/5) /(2/3) x(-5/6) / (3/4)

1 answer

To solve the given expression, we will use the properties of operations.

Step 1: Multiply the numerator and denominator of the first fraction:
(-2) x (1/5) = -2/5

Step 2: Multiply the numerator and denominator of the second fraction:
(2/3) x (-5/6) = (-10)/(18)

Step 3: Multiply the numerator and denominator of the third fraction:
(-10/18) / (3/4) = (-10/18) x (4/3)

Step 4: Simplify the multiplication:
(-10/18) x (4/3) = (-10 x 4) / (18 x 3) = (-40) / (54)

Step 5: Simplify the resulting fraction:
(-40) / (54) = -20/27

Therefore, the solution to the expression (-2) x (1/5) /(2/3) x(-5/6) / (3/4) is -20/27.